Radix Entomolaris in the Mandibular Molar Teeth of an Iranian Population - Maryam Kuzekanani; Laurence J. Walsh; Jahangir Haghani; Ali Zeynali Kermani (International Journal of Dentistry)
Purpose. Supernumerary roots in permanent mandibular molar teeth make endodontic treatment more complicated. The aim of this study was to determine the prevalence of Radix Entomolaris (RE) in permanent mandibular first and second molars in the population of Kerman, in the southeast of Iran. Materials and Methods. From a collection of 500 mandibular first and second molar teeth extracted over 2015-2016 at dental clinics in Kerman, teeth were scored for an additional distolingual root, and the average root length and root morphology of this extra root were determined using the De Moor classification scheme. Results. In this population, RE occurred in 6% of mandibular first molars (4% with a straight apex (Type I) and 2% with buccal apical curvature (Type III)). In all cases, RE was the shortest root, with an average root length of 18.37 mm. RE occurred in only 0.8% of mandibular second molars, with an average root length of 18.0 mm. All mandibular second molars with RE were of Type III. Fisher’s exact test showed that the difference in frequency between first and second molars was statistically significant (two-sided P=0.002). Conclusion. Radix Entomolaris occurs more frequently in mandibular first molars than in mandibular second molars in this sample of 500 mandibular molars. The reported rate of 6% in first molars is expected to be higher than reported rates in European or Caucasian populations where the prevalence is typically less than 2%.